On Becoming a Cybernetician: Highlights and Milestones. Issue 1 (17th February 2019) - Scott, Bernard
Abstract : In this article, I describe how I encountered cybernetics and how it became an important part of my life. I begin with an account of my time at Brunel University and also describe how I came to work with Gordon Pask, one of the few intellectuals and researchers in the UK who styled themselves as cyberneticians. To enrich my story, I include an overview of the story of cybernetics as I perceive it. Given the importance I attach to cybernetics as an intellectual tool, I end with a plea for it to be included in all educational curricula.